CULTURE AND ITS IMPACT ON THE WORKING PERFORMANCE OF GOVERNMENT STAFF THROUGH JOB SATISFACTION - Purnamie Titisari (Universitas Hayam Wuruk Perbanas, 2012)
The factor of culture in connection with job satisfaction appears prominent nowadays. Thisstudy attempts to determine the direct influence of culture on the job performance of CivilServants. It also determines the direct effect of job satisfaction on the performance of CivilServants as well as to determine the indirect influence of culture on job performance throughjob satisfaction of Civil Servants. This research was conducted at the Office of Tourism andCulture Jember district for 60 days by giving questionnaires to the existing Civil Servant inthe Office of Tourism and Culture Jember district using census techniques where the sampleis all of the existing Civil Servants in the Office of Tourism and Culture Jember regency consistingof 22 people. Research method used explanatory research to explain the influenceamong the variables. Data were analyzed using path analysis. The results show that there isa direct influence of culture on job performance by 72.5%, on job satisfaction performanceby 35.6%, and there is no direct link between culture and job performance through job satisfactionof 20.9%.